PENGARUH SERVICE QUALITY TERHADAP UTILITY KONSUMEN PADA RIAU FANTASI LABERSA WATER & THEME PARK PEKANBARU - HERISPON, HERISPON; Hartori, Rafly Aldilla (Eko dan Bisnis: Riau Economic and Business Review, 2020)
The purpose of this study was to determine the effect of service quality on consumer utility. The object of this research is Riau Fantasi Company Labersa Water & Theme Park Pekanbaru. Sampling was used random sampling. The population in this study were all customers of Riau Fantasi Labersa Water & Theme Park Pekanbaru in 2019, namely 176,441 people. While the determination of the number of samples determined by the Slovin formula as many as 100 people. The data analysis used is the regression method. This study found that service quality has a significant effect on consumer utility. It can be concluded that service quality can be used as a tool and method to increase consumer utility and the level of visits to the company